HLA-DRB1*04:05 and HLA-DQB1*04:01: Alleles Potentially Associated with Vogt-Koyanagi-Harada in Northern Thai Patients. (17th February 2021) - Anukul, Nampeung; Pathanapitoon, Kessara; Leetrakool, Nipapan; Guntiya, Tiphakorn; Wita, Ratsameetip; Palacajornsuk, Poonsub; Klangsinsirikul, Phennapha
ABSTRACT: Purpose: To determine the frequency and association of alleles at human leukocyte antigen (HLA)- DRB1 and HLA-DQB1 loci in VKH disease patients from Northern Thailand. Methods: A case–control study was conducted with three subject groups: 23 VKH patients, 20 patients with other uveitis entities, and 40 healthy blood donors. HLA-DRB1 and HLA-DQB1 loci were analyzed and the frequency of HLA-DRB1 and HLA-DQB1 alleles was calculated by direct counting. The measure of association was calculated by odds ratio (OR) and 95% confidence interval. Results: In VKH patients, the most prevalent allele was HLA-DRB1*04:05, found in 35% of patients and with the highest OR (42.13). HLA-DQB1*04:01 was the next most prevalent, found in 23.91% of VKH patients. HLA-DQB1*05:02 was also detected in 23.91% of patients; however, a higher prevalence was observed in non-VKH and healthy controls (30% and 35%, respectively). Conclusion: HLA-DRB1*04:05 and HLA-DQB1*04:01 could be potential genetic markers for VKH.